The Assessment of TLR1 Gene Polymorphism Association with the Risk of Allergic Rhinitis in the Chinese Han Population from Northern China - Han H; Lian P; Chen H; Shamsi BH; Liu Y; Niu Y (Journal of Asthma and Allergy, 2023)
Hui Han,1 Penggang Lian,2 Haiyuan Chen,3 Bilal Haider Shamsi,4 Yonglin Liu,4 Yongliang Niu5 1Clinical Laboratory, Shenmu Hospital, the Affiliated Shenmu Hospital of Northwest University, Shenmu, 719300, People’s Republic of China; 2Otorhinolaryngologic Department, Shenmu Hospital, the Affiliated Shenmu Hospital of Northwest University, Shenmu, 719300, People’s Republic of China; 3Information Department, Shenmu Hospital, the Affiliated Shenmu Hospital of Northwest University, Shenmu, 719300, People’s Republic of China; 4Department of Science and Education, Shenmu Hospital, the Affiliated Shenmu Hospital of Northwest University, Shenmu, 719300, People’s Republic of China; 5Department of Respiratory and Critical Care Medicine, Shenmu Hospital, the Affiliated Shenmu Hospital of Northwest University, Shenmu, 719300, People’s Republic of ChinaCorrespondence: Yongliang Niu, Tel/Fax +86-13892234287, Email niuyl7312@126.comBackground: Environmental factors and genetic predisposition can influence the occurrence and development of AR. Toll-like receptor 1 (TLR1) belongs to the TLR receptor family, which plays a fundamental role in the activation of innate immunity. This study aimed to explore the association between TLR1 genetic loci and AR susceptibility in the Han Chinese from northern China.Methods: Genotyping of three SNPs in the TLR1 has proceeded using the Agena MassARRAY platform. Odds ratio (OR) and 95% confidence interval (CI) were used to assess the correlation between candidate SNPs and AR susceptibility. Using FPRP (false-positive report probability analysis) to detect whether the positive results are noteworthy findings. The SNP-SNP interactions were detected by multifactor dimensionality reduction (MDR).Results: TLR1-rs72493538 (Allele “G”: OR=0.77, p = 0.034) and -rs76600635 (Allele “G”: OR=0.75, p = 0.024) were associated with reducing the risk of AR among Han Chinese in northern China. In addition, we found evidence that TLR1-rs72493538 (males, participants with aging > 43 years, or coming from the wind-blown sand region) and -rs76600635 (males, participants with BMI ≤ 24 kg/m2, or coming from the wind-blown sand region) were associated with AR risk in stratified analyses. FPRP showed that all positive results are noteworthy findings. MDR analysis showed that a two-loci genetic model composed of rs72493538 and rs76600635 can be chosen as the best genetic model to predict the risk of AR.Conclusion: TLR1-rs72493538 and -rs76600635 have a close association with reducing the risk of AR.Keywords: allergic rhinitis, TLR1, susceptibility, case-control study